A "mindful rational living" approach for addressing HIV in the school setting. Issue 2 (2nd April 2016) - Chenneville, Tiffany; St. John Walsh, Audra
Abstract : This paper describes a "mindful rational living" approach, which incorporates mindfulness techniques with rational emotive behavioral therapy strategies for addressing HIV in the school setting. The utility of this approach for attending to the physical, mental, and psychosocial aspects of school-based HIV prevention and treatment will be provided within existing multitier models of intervention.